ANTECEDENTS OF PURCHASE INTENTION OF BEAUTY PRODUCTS IN THE MARKETPLACE - Shakila Zahra; Indri Styawati; Aang Curatman (Journal of Management Small and Medium Enterprises (SMEs), 2025)
The purpose of this study is to investigate how perceivable usefulness (PU) and user-generated content (UGC) affect purchase intention (PI), as well as how consumer attitude (CA) functions as a mediator between PU and PI. The validity and reliability of the measurement model are tested using Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 4. The findings demonstrate that CA affects PI, PU affects CA, and UGC affects PI. Furthermore, PI is directly impacted by PU, and the impact of PU on PI is demonstrated to be mediated by CA. However, this study is limited to evaluating the measurement model without analysing causal relationships. Future research is recommended to test structural relationships and to apply this model to different consumer segments and industries. Keywords: User Generated Content; Perceived Usefulness; Consumer Attitude; Purchase Intention